Pembelajaran Mandiri dan Dampaknya terhadap Kompetensi Diri yang Lebih Nyata serta Pengendalian Diri yang Konsisten - Savira Widya Puspitasari; Fauzan Hidayatullah; Tri ’Ulya Qodriyati (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
Non-formal education serves as a strategic pathway for adult learners who require flexibility and life-relevant learning. However, qualitative studies examining the role of Self-Directed Learning (SDL) in shaping authentic self-competence and consistent self-control remain limited. This study aims to explore the experiences of learning citizens in implementing SDL and its impact on self-competence and the stability of self-control. This research employed a qualitative approach with a case study design conducted in several Community Learning Centers (PKBM) in Malang Regency and Malang City. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using an inductive thematic approach. The findings indicate that SDL fosters more authentic self-competence through personal goal setting, contextual learning strategies, and experiential self-evaluation. In addition, SDL strengthens consistent self-control through emotional regulation, time management, perseverance, and reflective decision-making. SDL is not merely a single skill but a pedagogical process influenced by tutor support, learning flexibility, and social-collaborative interaction. The implications highlight the importance of non-formal learning designs that provide structured autonomy, reflective practices, and self-regulatory support to enhance authentic competencies and self-control among learning citizens.